2016
DOI: 10.1007/s00253-016-7516-6
|View full text |Cite
|
Sign up to set email alerts
|

Different inocula produce distinctive microbial consortia with similar lignocellulose degradation capacity

Abstract: Despite multiple research efforts, the current strategies for exploitation of lignocellulosic plant matter are still far from optimal, being hampered mostly by the difficulty of degrading the recalcitrant parts. An interesting approach is to use lignocellulose-degrading microbial communities by using different environmental sources of microbial inocula. However, it remains unclear whether the inoculum source matters for the degradation process. Here, we addressed this question by verifying the lignocellulose d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 28 publications
4
70
0
Order By: Relevance
“…Other studies obtained similar degradation levels (between 40 and 50% average of all three lignocellulosic fractions [28, 29] with more than 20 different identified strains in the community). Here, we could identify a total of seven synthetic communities with optimal degradation levels.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Other studies obtained similar degradation levels (between 40 and 50% average of all three lignocellulosic fractions [28, 29] with more than 20 different identified strains in the community). Here, we could identify a total of seven synthetic communities with optimal degradation levels.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, we used enzymatic and metabolic-profile assessments to determine the degradation potential and metabolic property of the isolated members of the community. Enzymatic assessments are rather simple, powerful, and quantitative approaches for screening purposes and have been effectively used in analyzing lignocellulose degradation capacities [26, 29, 40]. Here, we used this method for screening purposes, focusing only on enzymes from the GH family, which are related to hemicellulose and cellulose degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Cortes-Tolalpa et al (2016) reported that inoculum source is also a key factor that strongly influences the composition of plant biomass-degrading microbial consortia. However, stochastic factors (“first come, first bite”) might also have affected the selection process and so driven the microbial diversity in the consortia.…”
Section: Discussionmentioning
confidence: 99%
“…; Cortes‐Tolalpa et al . ). The microbial origin, the genomic context and the annotation of the genes for these selected GHs all suggest that they play an important role in plant biomass degradation (Jiménez et al .…”
Section: Discussionmentioning
confidence: 97%